Nature-Derived and Synthetic Additives to poly(ɛ-Caprolactone) Nanofibrous Systems for Biomedicine; an Updated Overview - Homaeigohar, Shahin; Boccaccini, Aldo R. (Frontiers in Chemistry, 2022)
As a low cost, biocompatible, and bioresorbable synthetic polymer, polycaprolactone (PCL) is widely used for different biomedical applications including drug delivery, wound dressing, and tissue engineering. An extensive range of in vitro and in vivo tests has proven the favourable applicability of PCL in biomedicine, bringing about the FDA approval for a plethora of PCL made medical or drug delivery systems. This popular polymer, widely researched since the 1970s, can be readily processed through various techniques such as 3D printing and electrospinning to create biomimetic and customized medical products. However, low mechanical strength, insufficient number of cellular recognition sites, poor bioactivity, and hydrophobicity are main shortcomings of PCL limiting its broader use for biomedical applications. To maintain and benefit from the high potential of PCL, yet addressing its physicochemical and biological challenges, blending with nature-derived (bio)polymers and incorporation of nanofillers have been extensively investigated. Here, we discuss novel additives that have been meant for enhancement of PCL nanofiber properties and thus for further extension of the PCL nanofiber application domain. The most recent researches (since 2017) have been covered and an updated overview about hybrid PCL nanofibers is presented with focus on those including nature-derived additives, e.g. polysaccharides and proteins, and synthetic additives, e.g., inorganic and carbon nanomaterials.